THE CONTRIBUTION OF THE FISHERMAN WIFE TO THE INCOME OF FISHERMAN HOUSEHOLD IN TUKKO BARU VILLAGE SUBDISTRICT TAPANULI TENGAH REGENCY NORTH SUMATERA PROVINCE - Sarifah Simatupang; Darwis AN Darwis AN; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACK                Research on the contribution of fisherman's wife to fisherman's household income in LubukTukkoBaru Sub-district of Pandan District of Tapanuli Tengah Regency was conducted in February. This study aims to: 1) Identify the types of work of workers' wives to increase the income of fisherman households; 2) Knowing the outpouring of working wives of workers' wives to increase the income of fishermen households; 3) Knowing the contribution of the fisherman's wife to the income of fisherman's household.The method usedinthisresearchis the method ofsurveysamplingpurposive samplingas many as16 wivesof fishermen.               The results of the study indicate that the fishermen's wife has a significant role in supporting the household economy. The wife's role in helping her husband earn a living makes the wife do double roles in the household. The contribution of the fisherman's wife to the household income is done by the work / activity which includes; as rubber tappers, fishery product processors, fish sellers, day traders and as tailors. The biggest contribution of the five jobs performed by the fisherman wife is as rubber tappers, and it can be concluded that alternative activities can be developed that is with SMEs (Micro Small Medium Enterprises)Keywords: Contribution wife, North Sumatera Revenue